1986
DOI: 10.1128/iai.51.1.37-42.1986
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a gene involved in regulation of exotoxin A expression in Pseudomonas aeruginosa

Abstract: We have cloned a gene from Pseudomonas aeruginosa that stimulates the expression of exotoxin A. A recombinant library of genomic DNA from strain PA103 constructed with a broad-host-range plasmid vector containing chromosomal insert fragments generated by Sau3A was used to transform the hypotoxigenic mutant strain PA103-29. A recombinant plasmid, pFHK6, was isolated from a PA103-29 transformant which displayed increased toxin production. From pFHK6, which contained a 20-kilobase-pair chromosomal insert, a 3-kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 32 publications
2
33
1
Order By: Relevance
“…3B). However, these results appear to contrast with those reported by Hedstrom et al (1986) and with the results shown in Fig. 8B.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…3B). However, these results appear to contrast with those reported by Hedstrom et al (1986) and with the results shown in Fig. 8B.…”
Section: Discussioncontrasting
confidence: 99%
“…It is of interest that a strain which lacks the ETA structural gene (WR5) apparently still has all the factors necessary to regulate the synthesis of ETA at the transcriptional level. In this regard, Hedstrom et al (1986) have shown that this strain carries sequences homologous to the regulatory gene toxR. However, whether this gene or its product and the ETA promoter are sufficient to regulate synthesis of ETA remains to be determined (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of exotoxin A production in P. aeruginosa is a complicated process that involves several genes including regA, regB, fur, vfr, and lasR (Hedstrom et al, 1986;Hindahl et al, 1987;Wozniak et al, 1987;Wick et al, 1990a;Prince et al, 1991;West et al, 1994a;Gambello et al, 1993). The most extensively analysed of these genes is regA, which enhances toxA transcription.…”
Section: Introductionmentioning
confidence: 99%
“…These include lasR, a global regulator of protease production (Gambello et al, 1993), agmR, which is involved in regulation of glycerol metabolism genes (Po and Schweizer, 1993), anr, an oxygen responsive regulator (Sawers, 1991), fur, which regulates gene expression in response to iron levels (Prince et al, 1991;Prince, 1992), vfr, a cyclic AMP receptor homologue, (West et al, 1994), and most recently pvdS, an alternative sigma factor that regulates production of both iron uptake genes and ETA production (Ochsner et al, 1996). The regAB locus has the greatest and most direct effect on production of ETA (Hedstrom et al, 1986;Hindahl et al, 1987;Frank and Iglewski, 1988;Frank et al, 1989;Storey et al, 1991). The regA gene was cloned by complementation of a chemical mutant of P. aeruginosa defective in production of ETA, PA103-29 (Hedstrom et al, 1986).…”
Section: Introductionmentioning
confidence: 99%